A 20-year intellectual journey with “EMES” through the land of social enterprise - Nyssens, Marthe; Defourny, Jacques; Adam, Sophie (Social enterprise journal, 2023)
Purpose In 2022, the EMES Network celebrated its 20th anniversary. The purpose of this paper is to trace the intellectual path of social enterprise (SE) research that has unfolded through some of the major EMES research projects. Design/methodology/approach This journey is recounted through three major milestones: the emergence and development of the EMES approach; the identification of various SE schools of thought; the International Comparative Social Enterprise Models (ICSEM) Project. Findings The first section digs into the roots of the EMES approach – an ideal-type which allowed researchers to explore an SE field that was then largely unknown. In a second stage, a reading grid was developed to identify the different SE conceptions, their convergences and their divergences. In a third step, the ICSEM Project, acknowledging the impossibility to provide a single, universal definition of SE, aimed to identify SE models across the world. Defourny and Nyssens developed an SE typology and made the hypothesis that it was neither country-specific nor even context-specific. Based on the EMES ideal-type (which constituted a particularly relevant tool to inform the diversity of SE models), data were collected on over 700 SEs worldwide; three major SE models were found in almost all the countries covered. Originality/value This contribution does not aim to summarise all the – numerous and fruitful – research projects carried out by EMES members, but to show the common thread that runs through several of them.